Mechanism‐Based Inhibitor of DNA Cytosine‐5 Methyltransferase by a SNAr Reaction with an Oligodeoxyribonucleotide Containing a 2‐Amino‐4‐Halopyridine‐C‐Nucleoside. (14th March 2018) - Sato, Kousuke; Kunitomo, Yuma; Kasai, Yukiko; Utsumi, Shohei; Suetake, Isao; Tajima, Shoji; Ichikawa, Satoshi; Matsuda, Akira
Abstract: In chromatin, 5‐methylcytosine (mC), which represents the fifth nucleobase in genomic DNA, plays a role as an inducer of epigenetic changes. Tumor cells exhibit aberrant DNA methylation patterns, and inhibition of human DNA cytosine‐5 methyltransferase (DNMT), which is responsible for generating mC in CpG sequences, is an effective strategy to treat various cancers. Here, we describe the design, synthesis, and evaluation of the properties of 2‐amino‐4‐halopyridine‐ C ‐nucleosides (d X P) and oligodeoxyribonucleotides (ODNs) containing d X P as a novel mechanism‐based inhibitor of DNMTs. The designed ODN containing X PpG forms a complex with DNMTs by covalent bonding through a nucleophilic aromatic substitution (SN Ar) reaction, and its cell proliferation activity is investigated. This study suggests that d X P in a CpG sequence of DNA could serve as a potential nucleic acid drug lead in cancer chemotherapy and a useful chemical probe for studies of epigenetics. Our molecular design using a SN Ar reaction would be useful for DNMTs and other protein–DNA interactions. Abstract : SN Ar reaction on DNMTs : Oligodeoxyribonucleotides containing 2‐amino‐4‐halopyridine‐ C ‐nucleosides (d X P) at the CpG site form a covalent complex with DNA cytosine‐5 methyltransferases (DNMTs) through a nucleophilic aromatic substitution (SN Ar) reaction. DNA containing d X P in a CpG sequence could be a useful chemical probe for studies of epigenetics and a potential nucleic acid drug lead in cancer chemotherapy.